EVALUATION OF TOTAL PHENOLIC, FLAVONOIDAL CONTENT, AND DPPH FREE RADICAL SCAVENGING ACTIVITY OF METHANOLIC EXTRACT OF AILANTHUS EXCELSA ROXB. - Kumari, Aruna; Ra, Sharma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Estimation of total phenol, flavonoid and antioxidant activity of various plant parts (leaves, stem, root, flower and fruit) of Ailanthus excelsa Roxb. methanolic extracts. Methods: Different plant parts were extracted with methanol, then the total phenol content was calculated by using Folinâ€“Ciocalteu reagent, total flavonoid content was estimated by using Aluminum Chloride Colorimetric Method and the antioxidant activity was measured by DPPH (1,1-diphenyl-2-picrylhydrazyl radical) assay. Results: The highest total phenolic content (48.38 mg GAE/gdw) was observed in flower and lowest phenolic content in root (28.56 mg GAE/gdw). The highest total flavonoidal content (21.5 mg QE/gdw) was found in leaf and lowest in root (1.11 mg QE/gdw). The highest radical scavenging activity was found in flower extracts with the IC50 value of 36.85 Âµg/ml and the lowest scavenging activity was observed in root extract that was found to be 1493.46Âµg/ml. Conclusion: According to the results of present investigation the plant showed significant antioxidant activity that can be used for medical purpose for the treatment of various diseases. Keywords: Antioxidant activity, Ailanthus excelsa Roxb., Total phenolic content, Total flavonoid content, DPPH (2, 2- diphenyl- 1- picryl hydrazyl), Scavenging activity. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â